2016
DOI: 10.1177/0884533616656339
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Risk Screening in Patients Admitted to an Adult Emergency Department of a Brazilian University Hospital

Abstract: The prevalence of nutrition risk in emergency patients was high and its profile associated with worse clinical, laboratory, and anthropometric outcomes. The use of other laboratory and clinical variables may also be a good strategy for predicting adverse outcomes in emergency units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
8
2
1
Order By: Relevance
“…The highest and lowest prevalence rates of nutrition risk in the current study were identified from the MUST (37.1%) and NRS‐2002 (29.4%), lower than those described by Kami et al, who found nutrition risk for 48.7% (NRS‐2002) of the inpatients admitted to an emergency service in a Brazilian hospital 28 . Another study conducted in Brazilian hospitals detected similar proportions of patients at nutrition risk via the same instruments: 39.6% with the MUST and 27.1% with the NRS‐2002 (27.1%) 23 .…”
Section: Discussioncontrasting
confidence: 86%
“…The highest and lowest prevalence rates of nutrition risk in the current study were identified from the MUST (37.1%) and NRS‐2002 (29.4%), lower than those described by Kami et al, who found nutrition risk for 48.7% (NRS‐2002) of the inpatients admitted to an emergency service in a Brazilian hospital 28 . Another study conducted in Brazilian hospitals detected similar proportions of patients at nutrition risk via the same instruments: 39.6% with the MUST and 27.1% with the NRS‐2002 (27.1%) 23 .…”
Section: Discussioncontrasting
confidence: 86%
“…We have found no studies applying NRS-2002 to the population of interest in the ED. Two studies in individuals above the age of 18 reported prevalences of 29% and 49% [ 54 , 55 ], which are lower than the prevalence of 59% that we observed. This, we expect to be largely explained by the younger average age.…”
Section: Discussioncontrasting
confidence: 97%
“…A multicentre longitudinal study involving 564 063 patients admitted to Dutch hospitals also demonstrated a 1.4‐day longer hospital stay in patients with nutritional risk compared to those without nutritional risk (also according to the original MUST) . In addition, a prospective Brazilian study of 234 patients from the emergency unit of a general hospital showed that, for every 10 patients at nutritional risk, four stayed >10 days in the hospital . Another prospective observational study involving 537 patients with stroke also showed a positive association between the presence of nutritional risk according to the original MUST and mortality; in patients with high nutritional risk, the risk of death was 5.6‐fold higher (95% CI = 3.23–9.96) than in patients with low nutritional risk .…”
Section: Discussionmentioning
confidence: 94%